THEORETICAL PERSPECTIVES OF THE PRE-SERVICE ENGLISH LANGUAGE TEACHER EDUCATION PROGRAM: THE KNOWLEDGE BASE AND CURRICULUM - Nuraeni . (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2021)
This short contribution is a brief theoretical perspective of English Language Teacher Education (ELTE) from the existing theories started from 1985 to 2014. It reviews the theories of English language teacher education around the globe and in Indonesia. The main focus of this article is concerned with the knowledge base and the curriculum viewed from various perspectives. To link the theories of English language teacher education in Indonesia with the needs of school context, an overview of the existing curriculum at secondary level adds further description.